A chitinase CsChi23 promoter polymorphism underlies cucumber resistance against Fusarium oxysporum f. sp. cucumerinum. Issue 4 (30th September 2022) - Bartholomew, Ezra S.; Xu, Shuo; Zhang, Yaqi; Yin, Shuai; Feng, Zhongxuan; Chen, Shuyinq; Sun, Lei; Yang, Songlin; Wang, Ying; Liu, Peng; Ren, Huazhong; Liu, Xingwang
Summary: Fusarium wilt disease, caused by Fusarium oxysporum f. sp. cucumerinum ( Foc ), leads to widespread yield loss and quality decline in cucumber. However, the molecular mechanisms underlying Foc resistance remain poorly understood. We report the mapping and functional characterisation of CsChi23, encoding a cucumber class I chitinase with antifungal properties. We assessed sequence variations at CsChi23 and the associated defence response against Foc . We functionally characterised CsChi23 using transgenic assay and expression analysis. The mechanism regulating CsChi23 expression was assessed by genetic and molecular approaches. CsChi23 was induced by Foc infection, which led to rapid upregulation in resistant cucumber lines. Overexpressing CsChi23 enhanced fusarium wilt resistance and reduced fungal biomass accumulation, whereas silencing CsChi23 causes loss of resistance. CsHB15, a homeodomain leucine zipper (HD‐Zip) III transcription factor, was found to bind to the CsChi23 promoter region and activate its expression. Furthermore, silencing of CsHB15 reduces CsChi23 expression. A single‐nucleotide polymorphism variation −400 bp upstream of CsChi23 abolished the HD‐Zip III binding site in a susceptible cucumber line. Collectively, our study indicates that CsChi23 is sufficient to enhance fusarium wilt resistance and reveals a novel function of an HD‐Zip III transcription factor in regulating chitinase expression in cucumber defence against fusarium wilt.